Steel with improved processability for high temperature operation
By reasonably equipping the thermoformed flat steel products with aluminum and vanadium to form refined austenite structure and vanadium carbonitride distribution, the problem of poor processing performance of metal molded plate components in the prior art during the thermoforming process is solved, and higher mechanical properties and welding performance are achieved.
Patent Information
- Application Number
- CN202380059929.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-08-18
- Filing Date
- 2023-08-15
- Publication Date
- 2025-03-28
AI Technical Summary
The prior art is difficult to improve the processing performance of metal-formed panel components during the thermoforming process, especially when combined with an aluminum-based anti-corrosion coating.
A flat steel product for thermoforming is used, whose steel substrate contains specific components, including 0.06% to 1.0% aluminum, 0.01% to 0.50% vanadium, and other elements such as Ce, La, Ti, Nb, Cr, Cu, Mo, Ni, Ca and W. Through the reasonable proportion of these elements, a refined austenite structure and vanadium carbon nitride distribution are formed, improving the mechanical properties of metal molded plate components.
By increasing the aluminum content and adding elements such as vanadium, the formation of pores during the thermoforming process is significantly reduced, the mechanical integrity and welding performance of metal-formed plate components are improved, and its stability to hydrogen embrittlement is enhanced.
Smart Images

Figure BDA0005272187750000271 
Figure BDA0005272187750000341 
Figure BDA0005272187750000351
Abstract
Description
[0001] The invention relates to a flat steel product for hot forming and a method for producing such a flat steel product. The invention also relates to a metal profiled sheet metal component having improved properties and a method for producing such a metal profiled sheet metal component from a flat steel product.
[0002] In the following discussion of "flat steel products" or "sheet metal products", this refers to rolled products, such as steel strips or sheets, wherein a "sheet metal blank" (also called blank) is distinguished for the production of, for example, body parts. A "formed metal sheet component" or "sheet metal component" of the type according to the invention is already produced from such a sheet metal blank; the terms "formed metal sheet component" and "sheet metal component" are used synonymously here.
[0003] Unless expressly stated otherwise, all figures reported in this application relating to the contents of steel compositions are based on weight. Therefore, all ambiguous percentage figures relating to steel alloys should be considered as figures expressed in "% by weight". Except for the statements relating to the retained austenite content of the structures of the metal-formed sheet parts of the present invention, which are based on volume (reported in "% by volume"), the figures relating to the contents of the various structural components are based on the area of the cross-section of a sample of the corresponding product (reported as area percentage, "area %"), unless expressly stated otherwise. The figures given herein for the contents of atmospheric components are based on volume (reported in "% by volume").
[0004] Unless explicitly stated otherwise, the mechanical properties reported herein such as tensile strength, yield point and elongation have been determined in a tensile test in accordance with DIN-EN ISO 6982-1 Sample Form 2 (Annex B Table B1) (Edition 2020-06). The bending angle at maximum force was determined in accordance with VDA-Norm 238-100. In addition, the bending angle was determined at a thickness of 1.5 mm for the metal profiled sheet metal parts.
[0005] The structure was determined on longitudinal sections which had been etched with 3% Nital (alcoholic nitric acid). The proportion of retained austenite was determined by X-ray diffraction.
[0006] WO2019 / 223854A1 discloses a metal profiled plate component and a method for manufacturing such a metal profiled plate component, the metal profiled plate component having a tensile strength of at least 1000 MPa. The metal profiled plate component is composed of steel, which is composed of iron, 0.10%-0.30% C, 0.5%-2.0% Si, 0.5%-2.4% Mn, 0.01%-0.2% Al, 0.005%-1.5% Cr, 0.01%-0.1% P, unavoidable impurities and optional other optional elements (especially 0.005%-0.1% Nb) (in weight %). In addition, the metal profiled plate component includes an anti-corrosion coating containing aluminum.
[0007] EP3483299A1 discloses a metal profiled sheet metal component and a method for producing such a metal profiled sheet metal component. The metal profiled sheet metal component consists of steel, which consists of iron, unavoidable impurities and the following components (in weight %): 0.27%-0.40% C, 0.2%-3.0% Mn, 0.11%-0.4% V, 0-0.8% Si, 0-0.5% Al, 0-2% Cr, 0-0.15% Ti, 0-0.15% Nb, 0-0.004% B and less than 2% Mo, Ni and Cu in total.
[0008] WO 2020 / 239905 A1 discloses a steel composition for hot forming having a high aluminum content of up to 0.130.
[0009] EP 2 553 133 B1 likewise discloses a metal profiled sheet metal component and a method for producing such a metal profiled sheet metal component.
[0010] Against the background of the prior art, the problem to be solved is to further develop flat steel products for hot forming so that improved processing properties of hot formed sheet metal parts are achieved, in particular in combination with an aluminum-based anti-corrosion coating. Furthermore, a method is required in which such sheet metal parts can be produced in practice.
[0011] In a first embodiment, the invention achieves the above-mentioned object by a flat steel product for hot forming, which comprises a steel substrate, which consists of steel, which consists of iron and unavoidable impurities, optionally one or more of the elements "Ce, La, Ti, Nb, Cr, Cu, Mo, Ni, Ca, W", and the following components (in wt. %):
[0012] C: 0.06%-0.5%,
[0013] Si: 0.05%-0.6%,
[0014] Mn: 0.4%-3.0%,
[0015] Al: 0.06%-1.0%,
[0016] B: 0.0005%-0.01%,
[0017] V: 0.010%-0.50%,
[0018] P: ≤0.03%,
[0019] S: ≤0.02%,
[0020] N: ≤0.02%,
[0021] Sn: ≤0.03%,
[0022] As: ≤0.01%,
[0023] The content of one or more of the optional elements "Ce, La, Ti, Nb, Cr, Cu, Mo, Ni, Ca, W" is:
[0024] Ce+La: 0.01%-0.03%,
[0025] Ti: 0.0005%-0.10%,
[0026] Nb: 0.001%-0.2%,
[0027] Cr: 0.01%-1.0%,
[0028] Cu: 0.01%-0.2%,
[0029] Mo: 0.002%-0.3%,
[0030] Ni: 0.01%-0.5%,
[0031] Ca: 0.0005%-0.005%,
[0032] W: 0.001%-1.00%.
[0033] The steel substrate of the flat steel product according to the invention has an aluminum content of at least 0.06% by weight, preferably at least 0.07% by weight, in particular at least 0.08% by weight. The aluminum content is preferably at least 0.10% by weight, more preferably at least 0.11% by weight, in particular at least 0.12% by weight, preferably at least 0.140% by weight, in particular at least 0.15% by weight, preferably at least 0.16% by weight. The maximum aluminum content is 1.0% by weight, in particular not more than 0.8% by weight, preferably not more than 0.50% by weight, in particular not more than 0.35% by weight, preferably not more than 0.25% by weight, in particular not more than 0.24% by weight.
[0034] It is known to add aluminum ("Al") as a deoxidizer in steelmaking. At least 0.01% by weight of Al is required for reliable bonding of the oxygen present in the steel melt. In addition, Al can be used additionally to bond N contents that are not required but are unavoidable for production-related reasons. So far, relatively high aluminum contents have been avoided because the Ac3 temperature also rises with the aluminum content. This has an adverse effect on austenitization, which is important for hot forming. In addition, above a content of about 0.24% by weight, the weldability of hot formed parts may gradually deteriorate. Therefore, the Al content is preferably limited to the upper end described in the previous paragraph, for example a maximum of 0.35% by weight. In addition, an increase in the aluminum content leads to an increase in the martensite start temperature and the necessary critical cooling rate during hot forming, which makes it more complicated. However, surprisingly, it has been found that an increased aluminum content (i.e., an aluminum content of at least 0.06% by weight) produces a positive effect, especially in combination with an aluminum-based anti-corrosion coating.
[0035] In the process of coating flat steel products with aluminum-based anticorrosion coatings and in the process of subsequently hot forming the metal sheet blanks thus divided into metal forming sheet parts, iron diffuses from the steel substrate into the liquid anticorrosion coating. In the interdiffusion zone, this forms an aluminum-iron compound with a relatively high density through a multi-stage phase transformation (Fe2Al5→Fe2Al→FeAl→Fe3Al). The formation of this denser phase is associated with a higher aluminum consumption compared to the less dense phase. This locally higher aluminum consumption leads to the formation of holes (defective points) in the resulting phase. These holes are preferably formed in the transition zone between the steel substrate and the anticorrosion coating, where the proportion of available aluminum is largely determined by the aluminum content of the steel substrate. In particular, there may be an accumulation of holes in the form of strips in the transition zone.
[0036] Such holes, and especially hole bands, cause various problems:
[0037] - The pores reduce the mechanical integrity in this area. There may be faster layer separation under corrosion stress.
[0038] Furthermore, after adhesive bonding or welding, the transmissible forces at the bonding point of the two components are reduced.
[0039] - Holes lead to changes in the current path in the material during resistance spot welding, which adversely affects the suitability of the weld and thus reduces the weld range.
[0040] -Even the holes themselves contribute to crack initiation and propagation during static and dynamic bending.
[0041] It has surprisingly been found that increasing the aluminum content (Al) in the steel substrate above the stated lower limit allows a significant reduction in pore formation during application of the aluminum-based anticorrosion coating and subsequent hot forming. In particular, in the transition region between the steel substrate and the anticorrosion coating, the locally higher aluminum consumption can be at least partially compensated by the aluminum content of the steel substrate in the case of the formation of denser aluminum-iron compounds, thereby suppressing the formation of pores, in particular the formation of pore bands.
[0042] In the case of too high Al content, in particular in the case of an Al content of more than 1.0 wt. %, there is a risk of forming Al oxides on the surface of the product made of the steel material alloyed according to the present invention, which will deteriorate the wetting properties in the hot dip coating operation. In addition, in the case of relatively high Al content, the formation of non-metallic Al-based inclusions is favorable, which as coarse inclusions have an adverse effect on the collision characteristics. In addition, too high an aluminum content will lead to significant diffusion into the coating. This will correspondingly reduce the silicon content in the anti-corrosion coating, which may impair the function of the anti-corrosion coating. Therefore, the Al content is preferably selected to be lower than the upper limit already mentioned.
[0043] The bending properties are specifically addressed here by the addition of vanadium (V). Vanadium is present in the steel of the flat steel product in a content of 0.010% by weight to 0.50% by weight. Above a vanadium content of 0.010% by weight, the degree of formation of vanadium carbonitrides increases. These compounds act as traps for hydrogen present in the steel, which would otherwise lead to embrittlement of the steel. The vanadium content is preferably at least 0.020% by weight, in particular at least 0.030% by weight, more preferably at least 0.050% by weight.
[0044] The vanadium content (as well as the optional niobium content explained below), in particular in the method described below for producing a hot-forming flat steel product with an anticorrosion coating, leads to a distribution of vanadium carbonitrides (or niobium carbonitrides) which produces a particularly fine hardened structure in the subsequent hot forming operation. During the cooling after the hot dip coating operation, the coated flat steel product is kept for a certain time in a temperature range between 400° C. and 300° C. In this temperature range, carbon (C) still has a certain diffusion rate in the steel matrix, while the thermodynamic solubility is very low. Therefore, carbon diffuses into lattice defects and collects at the lattice defects. Lattice defects are caused in particular by dissolved vanadium or niobium atoms, which, by virtue of their much higher atomic volume, expand the atomic lattice and thus increase the size of the tetrahedral and octahedral interstices in the atomic lattice, so that the local solubility of C increases. As a result, clusters of carbon and vanadium or niobium appear in the steel matrix and are then transformed into very fine precipitates in the subsequent austenitizing step of hot forming and act as additional austenite grains. The result is therefore a refined austenite structure with relatively small austenite grains and thus a refined hardness structure.
[0045] This also applies in particular to the ferrite interdiffusion layer formed during hot forming. The refined ferrite structure in the interdiffusion layer helps to reduce the tendency to initiate cracks under bending stress.
[0046] Furthermore, vanadium carbonitrides also precipitate during hot forming, for example during transfer from the heating device to the forming tool or during cooling after removal from the forming tool, thus resulting in a large number of particularly fine precipitates. These fine precipitates have a particularly favorable effect on strength and hydrogen stability.
[0047] At higher vanadium contents, increasingly coarse precipitates are formed. Such coarse precipitates can cause relatively significant deformations in the surrounding structure, which in turn can lead to accumulation of hydrogen and thus have more adverse effects, whereas finely distributed carbides form permanently bound relatively large amounts of hydrogen present. Furthermore, the addition of high levels of vanadium is not economically feasible. For good bending properties and, in particular, high stability to hydrogen embrittlement, the vanadium content is preferably not more than 0.50% by weight, in particular not more than 0.30% by weight, preferably not more than 0.20% by weight, particularly preferably 0.1% by weight, more preferably 0.08% by weight.
[0048] The elements vanadium, niobium and titanium all form precipitates that contribute to grain refinement. However, due to their different solubilities, the precipitates appear at different temperatures. Titanium nitride has the lowest solubility in austenite and therefore precipitates already at very high temperatures and reduces the grain growth of the austenite. Nb precipitates from moderate temperatures, while vanadium only precipitates below about 900°C. This means that vanadium leads to particularly fine precipitates. The contents of these three elements should therefore be adjusted precisely relative to each other and to the cooling process.
[0049] Optionally, the steel in the flat steel product according to the invention has a cerium (Ce) and lanthanum (La) content of more than 0.01% by weight. The expression Ce+La is greater than or less than a certain value means that cerium or lanthanum is present in the steel, or that cerium and lanthanum are present simultaneously, wherein the sum of the cerium and lanthanum contents in all three cases is greater than or less than the determined value. Thus,
[0050] Ce+La: 0.01 wt% - 0.03 wt%
[0051] This means that cerium or lanthanum or cerium and lanthanum are present in the steel, wherein the total content of cerium and lanthanum is 0.01% to 0.03% by weight. The content of Ce+La is preferably at least 0.010% by weight, in particular at least 0.015% by weight. Further preferably, the content of Ce+La is not higher than 0.025% by weight. Cerium and lanthanum are chemically very similar and therefore firstly have the same effect in the steel and secondly are difficult to distinguish from each other analytically. Therefore, it is appropriate to only consider the sum of the contents of cerium and lanthanum. Therefore, when indicating the addition of cerium and / or lanthanum, "cerium / lanthanum" is occasionally mentioned below.
[0052] Surprisingly, it has been found that even small additions of more than 0.01 wt. % Ce+La have a positive effect on the resistance to hydrogen embrittlement (and therefore on the bending properties). The corresponding addition leads to the formation of more effective hydrogen traps. Studies have shown that this is caused by effects including the formation of spherical oxysulfides of Ce and / or La (e.g. Ce2O2S). Compounds of Ce and La are formed already at very high temperatures and are thermodynamically very stable. They also ensure the binding of oxygen and sulfur for small amounts of Al2O3, MnS and similar inclusions.
[0053] In the case where the Ce+La content is too high, there may be "clogging" of the immersion tube during casting. Therefore, the Ce+La content is limited to 0.03% by weight.
[0054] The stability to hydrogen embrittlement is determined by a modified slow strain rate test according to DIN EN ISO 7539-7:2018-05. The test speed is 0.1 μm / s. The measurement is carried out at room temperature. The sample geometry is Figure 1 It is shown in detail in Figure 1 The distances given in should be considered as being in mm. The maximum fracture stress before failure of the specimen was determined. To test the influence of the hydrogen that had diffused in, the specimen was placed in the middle of an electrolyte cell filled with an aqueous electrolyte with 0.025% NH4SCN (ammonium thiocyanate). The loading current density was -0.025 mA / cm 2 In this way, the specimen is filled with hydrogen before and during the measurement. Hydrogen loading starts 80 minutes before mechanical stressing and is maintained until specimen failure. This ensures a uniform hydrogen concentration at the start of the test and prevents the release of hydrogen during the test. The fracture stress determined in this test serves as a measure of resistance to hydrogen embrittlement.
[0055] In general, the addition of aluminum, vanadium and cerium / lanthanum each has a positive effect on the bending properties. More preferably, the alloy contains aluminum and vanadium as well as cerium and / or lanthanum. However, even the inclusion of two of these three substances in the alloy provides an improvement over the prior art. Therefore, this object has been achieved by adding aluminum and vanadium, as explained in the first embodiment above. The inclusion of vanadium and cerium / lanthanum in the alloy (even without aluminum) also produces improved fracture characteristics. Therefore, the object of the present invention is also achieved by the following second embodiment.
[0056] In a second embodiment, the invention achieves the above-mentioned object by a flat steel product for hot forming, which comprises a steel substrate, which consists of steel, which consists of iron and inevitable impurities, optionally one or more of the elements "Al, Ti, Nb, Cr, Cu, Mo, Ni, Ca, W", and the following components (in wt%):
[0057] C: 0.06%-0.5%,
[0058] Si: 0.05%-0.6%,
[0059] Mn: 0.4%-3.0%,
[0060] B: 0.0005%-0.01%,
[0061] V: 0.010%-0.50%,
[0062] P: ≤0.03%,
[0063] S: ≤0.02%,
[0064] N: ≤0.02%,
[0065] Sn: ≤0.03%,
[0066] As: ≤0.01%,
[0067] Ce+La: 0.01%-0.03%,
[0068] The content of one or more of the optional elements "Al, Ti, Nb, Cr, Cu, Mo, Ni, Ca, W" is:
[0069] Al: ≤1.0%,
[0070] Ti: 0.0005%-0.10%,
[0071] Nb: 0.001%-0.2%,
[0072] Cr: 0.01%-1.0%,
[0073] Cu: 0.01%-0.2%,
[0074] Mo: 0.002%-0.3%,
[0075] Ni: 0.01%-0.5%,
[0076] Ca: 0.0005%-0.005%,
[0077] W: 0.001%-1.00%.
[0078] For the vanadium and cerium / lanthanum which must be used in the second embodiment, the same preferred ranges as for the first embodiment apply. For the optional aluminum here, the optional aluminum content is preferably at least 0.01% by weight, in particular at least 0.03% by weight, more preferably at least 0.06% by weight, preferably at least 0.07% by weight, and in particular at least 0.08% by weight. The aluminum content is preferably at least 0.10% by weight, more preferably at least 0.11% by weight, in particular at least 0.12% by weight, preferably at least 0.140% by weight, in particular at least 0.15% by weight, preferably at least 0.16% by weight. The maximum aluminum content is 1.0% by weight, in particular not more than 0.8% by weight, preferably not more than 0.50% by weight, in particular not more than 0.35% by weight, preferably not more than 0.25% by weight, and in particular not more than 0.24% by weight.
[0079] The following description of various elements and their preferred ranges applies to both the first and second embodiments.
[0080] Carbon (C) is present in the steel matrix of the flat steel product in a content of 0.06 wt. % to 0.5 wt. %. C contents set at such levels contribute to the hardenability of the steel, since they delay the formation of ferrite and bainite and stabilize the retained austenite in the structure. In order to achieve sufficient hardenability and the associated high strength, a C content of at least 0.06 wt. % is required.
[0081] However, high C content has an adverse effect on weldability. In order to improve weldability, the C content can be adjusted to 0.5 wt. %, preferably not more than 0.5 wt. %, especially not more than 0.45 wt. %, preferably 0.42 wt. %, more preferably 0.40 wt. %, preferably not more than 0.38 wt. %, especially not more than 0.35 wt. %, preferably not more than 0.33 wt. %. Further preferably, the C content is at least 0.20 wt. %, especially at least 0.25 wt. %, preferably at least 0.30 wt. %, especially at least 0.31 wt. %.
[0082] Silicon (Si) is used to further increase the hardenability of flat steel products and the strength of press-hardened products through solid solution strengthening. Silicon also enables the use of ferrosilicomanganese as an alloying agent, which has a beneficial effect on production costs. The hardening effect is already established when the Si content is above 0.05% by weight. When the Si content is at least 0.10% by weight, in particular at least 0.15% by weight, the strength is significantly improved. In addition, silicon is a relatively cheap alloying element, so it is economically advantageous to use Si to increase the strength. Si contents above 0.6% by weight have an adverse effect on coating properties, especially in the case of Al-based coatings. In order to improve the surface quality of the coated flat steel product, it is preferably set to a Si content of no more than 0.50% by weight, in particular no more than 0.30% by weight, and preferably no more than 0.25% by weight.
[0083] Manganese (Mn) is used as a hardening element because it significantly delays the formation of ferrite and bainite. When the manganese content is less than 0.4% by weight, a significant proportion of ferrite and bainite will be formed during the press hardening process even at very fast cooling rates, which should be avoided. When it is necessary to ensure a martensitic structure, in particular in relatively high-forming areas, a Mn content of at least 0.5% by weight, in particular at least 0.7% by weight, preferably at least 0.8% by weight, in particular at least 0.9% by weight, more preferably at least 1.0% by weight, in particular at least 1.05% by weight is advantageous. Mn content exceeding 3.0% by weight has an adverse effect on processing properties, so the Mn content of the flat steel product of the present invention is limited to no more than 3.0% by weight, preferably no more than 2.5% by weight. In particular, weldability is greatly limited, so the Mn content is preferably limited to no more than 1.6% by weight, in particular 1.30% by weight, in particular no more than 1.20% by weight. In addition, for economic reasons, it is also preferred that the manganese content does not exceed 1.6% by weight.
[0084] Boron (B) is included in the alloy to improve the hardenability of the flat steel product, because the boron atoms or boron precipitates adjacent to the austenite grain boundaries reduce the grain boundary energy, which inhibits the nucleation of ferrite during press hardening. In the case of a B content of at least 0.0005% by weight, preferably at least 0.0007% by weight, in particular at least 0.0010% by weight, in particular at least 0.0020% by weight, a significant effect on the hardenability is produced. On the contrary, in the case of a B content of more than 0.01% by weight, the formation of boron carbide, boron nitride or boron carbide increases, which in turn constitutes a preferred nucleation site for ferrite nucleation and reduces the hardening effect again. Therefore, the boron content is limited to not more than 0.01% by weight, preferably not more than 0.0100% by weight, preferably not more than 0.0050% by weight, in particular not more than 0.0035% by weight, in particular not more than 0.0030% by weight, preferably not more than 0.0025% by weight.
[0085] Phosphorus (P) and sulfur (S) are elements introduced into steel as impurities from iron ore and cannot be completely removed in industrial-scale steelmaking processes. Since the mechanical properties (e.g. notched impact resistance) deteriorate with increasing P or S content, the P content and S content should be kept as low as possible. In addition, when the P content exceeds 0.03% by weight, martensite begins to embrittle, so the P content of the flat steel product of the present invention is limited to not more than 0.03% by weight, in particular not more than 0.02% by weight. The S content of the flat steel product of the present invention is limited to not more than 0.02% by weight, preferably not more than 0.0010% by weight, in particular not more than 0.005% by weight.
[0086] Due to the steel manufacturing process, nitrogen (N) is also present in steel as an impurity in small amounts. The nitrogen content should be kept as low as possible and should not exceed 0.02% by weight. In particular, in the case of alloys containing boron, nitrogen is harmful because the formation of boron nitride prevents the transformation delay effect of boron, so in this case, the nitrogen content should preferably not exceed 0.010% by weight, in particular not exceed 0.007% by weight.
[0087] Other typical impurities are tin (Sn) and arsenic (As). The Sn content does not exceed 0.03% by weight, preferably does not exceed 0.02% by weight. The As content does not exceed 0.01% by weight, in particular does not exceed 0.005% by weight.
[0088] In addition to the impurities P, S, N, Sn and As described above, other elements may be present in the steel as impurities. These other elements are combined under "inevitable impurities". The content of these "inevitable impurities" preferably does not add up to 0.2% by weight, preferably does not add up to 0.1% by weight. The optional alloying elements Ce, La, Ti, Nb, Cr, Cu, Mo, Ni, Ca and W, which are specified below as lower limits, may also be present in the steel matrix as inevitable impurities in a content below the corresponding lower limit. In this case, they are also counted as "inevitable impurities" whose total content is limited to not more than 0.2% by weight, preferably not more than 0.1% by weight.
[0089] In a first embodiment, cerium, lanthanum, titanium, niobium, chromium, copper, molybdenum, nickel, calcium and tungsten may optionally be contained in the steel of the flat steel product according to the invention, each individually or in combination with one another.
[0090] In a second embodiment, aluminum, titanium, niobium, chromium, copper, molybdenum, nickel, calcium and tungsten may optionally be contained in the steel of the flat steel product according to the invention, each individually or in combination with one another.
[0091] Titanium (Ti) is a microalloying element optionally included in the alloy to assist in grain refinement, and at least 0.0005 wt. % Ti, in particular at least 0.0010 wt. % Ti, preferably at least 0.010 wt. % Ti should be added to obtain sufficient availability. Above 0.10 wt. % Ti, cold rollability and recrystallization properties deteriorate significantly, so any higher Ti content should be avoided. In order to improve cold rollability, the Ti content can be preferably limited to less than 0.08 wt. %, in particular less than 0.038 wt. %, more preferably less than 0.020 wt. %, in particular less than 0.015 wt. %. In addition, titanium has the effect of binding nitrogen, and thus allows boron to exert its great ferrite inhibition effect.
[0092] By optionally adding niobium (Nb) in an amount of at least 0.001 wt. %, the bending properties of the sheet metal component are even further improved. The Nb content is preferably at least 0.005 wt. %, in particular at least 0.010 wt. %, preferably at least 0.015 wt. %, more preferably at least 0.020 wt. %.
[0093] The mechanism of action of niobium has been elucidated together with that of vanadium, as the mechanisms for both elements are similar.
[0094] However, too high a Nb content leads to deterioration of recrystallization. Therefore, the Nb content does not exceed 0.2 wt %. Further preferably, the Nb content does not exceed 0.20 wt %, especially does not exceed 0.15 wt %, preferably does not exceed 0.10 wt %, especially does not exceed 0.05 wt %, preferably does not exceed 0.04 wt %, especially does not exceed 0.030 wt %.
[0095] Aluminum, niobium and vanadium have an effect on grain refinement during austenitization during hot forming. It has been found that aluminum and niobium, in particular, refine the grain growth of austenite at high temperatures (e.g., above 1200° C.) by relatively early formation of AlN (i.e., occurring at relatively high temperatures). The formation of AlN is thermodynamically preferred over the formation of NbN or NbC and VN or VC. Here, the precipitation of AlN has a grain refining effect in austenite and thus has a toughness-improving effect. An increase in the ratio of Al to the sum of the Nb and V contents improves this effect. Thus, there is optionally the case where the Al / (Nb+V) ratio of the Al content to the sum of the Nb and V contents is:
[0096] 1≤Al / (Nb+V);
[0097] Preferably, the Al / Nb ratio is ≥ 2. At the same time, an Al / (Nb+V) ratio that is too large has the effect that the formation of AlN is no longer advantageously fine, but that increasingly coarse AlN particles occur, which in turn reduces the grain refining effect. It is therefore advantageous to optionally establish the following Al / (Nb+V) ratio:
[0098] Al / (Nb+V)≤30.0
[0099] Preferably, the Al / (Nb+V) ratio is ≤20.0, especially ≤16.0, preferably ≤14.0, more preferably ≤12.0, especially ≤10.0, preferably ≤8.0, especially ≤6.0, preferably ≤4.0.
[0100] The chromium (Cr) which is optionally present suppresses the formation of ferrite and pearlite during the accelerated cooling of the flat steel product according to the invention and enables complete formation of martensite even at relatively low cooling rates, which results in an increase in the hardenability.
[0101] These stated effects are established for contents above 0.01 wt. %, and contents of at least 0.10 wt. %, preferably at least 0.15 wt. %, have been found to be useful in practice for reliable processing. However, too high Cr contents impair the coatability of the steel. Therefore, the Cr content of the steel of the steel substrate is limited to not more than 1.0 wt. %, preferably not more than 0.80 wt. %, in particular not more than 0.75 wt. %, preferably not more than 0.50 wt. %, in particular not more than 0.30 wt. %.
[0102] Copper (Cu) may optionally be included in the alloy to increase hardenability in an amount of at least 0.01 wt. %, preferably at least 0.010 wt. %, and in particular at least 0.015 wt. %. In addition, copper improves the atmospheric corrosion resistance of the uncoated sheet or cut edge. In the case of too high a Cu content, the hot rolling properties are significantly deteriorated due to the low melting point Cu phase on the surface, so the Cu content is limited to not more than 0.2 wt. %, preferably not more than 0.1 wt. %, and in particular not more than 0.10 wt. %.
[0103] Molybdenum (Mo) can be optionally added to improve processing stability because it significantly slows down the formation of ferrite. When the content is above 0.002 wt.%, molybdenum-carbon clusters are dynamically formed at the grain boundaries, up to including ultrafine molybdenum carbides, which significantly slow down the mobility of the grain boundaries and thus slow down the diffusion phase transformation. In addition, molybdenum reduces the grain boundary energy, thereby reducing the nucleation rate of ferrite. The Mo content is preferably at least 0.004 wt.%, in particular at least 0.01 wt.%. Due to the high costs associated with molybdenum alloying, the Mo content should not exceed 0.3 wt.%, preferably not more than 0.20 wt.%, in particular not more than 0.15 wt.%, in particular not more than 0.10 wt.%, preferably not more than 0.08 wt.%.
[0104] Nickel (Ni) stabilizes the austenite phase and can optionally be included in the alloy to reduce the Ac3 temperature and inhibit the formation of ferrite and bainite. In addition, nickel has a positive effect on hot rolling properties, especially when the steel contains copper. Copper can make hot rolling properties worse. In order to offset the adverse effects of copper on hot rolling properties, 0.01% by weight of nickel can be included in the alloy as part of the steel; the Ni content is preferably at least 0.015% by weight. For economic reasons, the nickel content should be kept limited to no more than 0.5% by weight, in particular no more than 0.20% by weight. The Ni content is preferably no more than 0.10% by weight.
[0105] Calcium (Ca) in steel serves to round off non-metallic inclusions, in particular manganese sulfides. The rounded off inclusions significantly reduce the negative effects of these inclusions on hot formability, continuous strength and toughness. In order to also utilize this effect in the case of the flat steel product according to the invention, the flat steel product according to the invention may optionally contain at least 0.0005% by weight of Ca, in particular at least 0.0010% by weight, preferably at least 0.0020% by weight. The maximum Ca content is 0.01% by weight, in particular not more than 0.007% by weight, preferably not more than 0.005% by weight. In the case of an excessively high Ca content, the likelihood of the formation of non-metallic inclusions containing Ca increases, which deteriorate the purity and toughness of the steel. Therefore, the upper limit of the Ca content to be observed should be no more than 0.005% by weight, preferably no more than 0.003% by weight, in particular no more than 0.002% by weight, preferably no more than 0.001% by weight.
[0106] Tungsten (W) can optionally be included in the alloy in an amount of 0.001 wt. % to 1.0 wt. % to slow down the formation of ferrite. A positive effect on hardenability has already occurred with a W content of at least 0.001 wt. %. For cost reasons, no more than 1.0 wt. % of tungsten is included in the alloy.
[0107] In a preferred development, the sum of the Mn content and the Cr content ("Mn+Cr") is greater than 0.7% by weight, in particular greater than 0.8% by weight, preferably greater than 1.1% by weight. Below a minimum sum of the two elements, their necessary conversion-inhibiting effect is lost. In any case, the sum of the Mn content and the Cr content is less than 3.5% by weight, preferably less than 2.5% by weight, in particular less than 2.0% by weight, more preferably less than 1.5% by weight. The above upper limits for both elements are a result of ensuring the coating properties and ensuring adequate welding properties.
[0108] The above statements regarding the element contents and their preferred limitations for the first and second embodiments apply correspondingly to the method for producing a flat steel product, the metal profiled sheet metal component and the method for producing a metal profiled sheet metal component described below.
[0109] The flat steel product preferably comprises an anti-corrosion coating in order to protect the steel substrate from oxidation and corrosion during the hot forming operation and during use of the produced steel component.
[0110] In a specific embodiment, the flat steel product preferably comprises an aluminum-based anticorrosion coating. This anticorrosion coating can have been applied on one or both sides of the flat steel product. "Both sides of the flat steel product" refers to the two opposite large faces of the flat steel product. The narrow faces are called edges.
[0111] Such an anticorrosion coating is preferably produced by hot-dip coating of the flat steel product. This involves running the flat steel product through a liquid melt consisting of: 0.1% by weight to 15% by weight Si, preferably more than 1.0% by weight Si; optionally 2% by weight to 4% by weight Fe; optionally up to 5% by weight alkali metal or alkaline earth metal, preferably up to 1.0% by weight alkali metal or alkaline earth metal; optionally up to 15% by weight Zn, preferably up to 10% by weight Zn; and optional other components limited to a total of not more than 2.0% by weight; the remainder being aluminum.
[0112] In preferred variants, the Si content of the melt is 1.0% to 3.5% by weight or 7% to 12% by weight, in particular 8% to 10% by weight.
[0113] In a preferred embodiment, the optional alkali metal or alkaline earth metal content in the melt comprises 0.1% to 1.0% by weight of Mg, in particular 0.1% to 0.7% by weight of Mg, preferably 0.1% to 0.5% by weight of Mg. Furthermore, the optional alkali metal or alkaline earth metal content in the melt may in particular comprise at least 0.0015% by weight of Ca, in particular at least 0.01% by weight of Ca.
[0114] In the case of hot-dip coating, iron diffuses from the steel substrate into the liquid coating, so that during solidification the corrosion protection coating of the flat steel product comprises, in particular, an alloy layer and an Al-based layer.
[0115] The alloy layer is located on the steel substrate and directly adjacent to the steel substrate. The alloy layer is basically formed by aluminum and iron. Other elements from the steel substrate or the melt composition will not significantly accumulate in the alloy layer. The alloy layer is preferably composed of 35% by weight to 60% by weight of Fe (preferably α-iron), optional other ingredients (its content is limited to a total of no more than 5.0% by weight, preferably 2.0% by weight) and the remainder of aluminum, wherein the Al content preferably rises in the surface direction. Optional other components especially include other components of the melt (that is, silicon and optional alkali metals or alkaline earth metals, especially Mg and Ca) and other components of the steel substrate except iron.
[0116] The Al-based layer is located on the alloy layer and directly adjacent to the alloy layer. The composition of the Al-based layer preferably corresponds to the composition of the melt in the melt pool. This means that it is limited to the optional other components and the aluminum composition of the surplus that are no more than 2.0 weight % by 0.1 weight %-15 weight % Si, optional 2 weight %-4 weight % Fe, optional 5.0 weight % at the most alkali metal or alkaline earth metal (preferably 1.0 weight % at the most alkali metal or alkaline earth metal), optional 15 weight % at the most Zn (preferably 10 weight % at the most) and content.
[0117] In a preferred variant of the Al-based layer, the optional alkali metal or alkaline earth metal content comprises 0.1 wt.-1.0 wt.-% Mg, in particular 0.1 wt.-0.7 wt.-% Mg, preferably 0.1 wt.-0.5 wt.-% Mg. In addition, the optional alkali metal or alkaline earth metal content in the Al-based layer can especially comprise at least 0.0015 wt.-% Ca, in particular at least 0.1 wt.-% Ca.
[0118] In another preferred variant of the corrosion protection coating, the Si content in the alloy layer is lower than the Si content in the Al-based layer.
[0119] The anti-corrosion coating preferably has a thickness of 5 μm to 60 μm, in particular 10 μm to 40 μm. The coating weight of the anti-corrosion coating is in particular 30 g / m in the case of a double-sided anti-corrosion coating. 2 -360g / m 2 , or 15 g / m in the case of the single-sided variant 2 -180g / m 2 Preferably, the coating weight of the anti-corrosion coating is 100 g / m 2 -200g / m 2 , or 50g / m2 in case of single-sided coating 2 -100g / m 2 More preferably, the coating weight of the anti-corrosion coating is 120 g / m 2 -180g / m 2 , or more preferably 60 g / m2 in the case of single-sided coating 2 -90g / m 2 .
[0120] The thickness of the alloy layer is preferably less than 20 μm, more preferably less than 16 μm, especially less than 12 μm, more preferably less than 10 μm, preferably less than 8 μm, especially less than 5 μm. The thickness of the Al-based layer is determined by the difference in thickness between the anticorrosion coating and the alloy layer. Even in the case of a thin anticorrosion coating, the thickness of the Al-based layer is preferably at least 1 μm.
[0121] In a preferred variant, the flat steel product comprises an oxide layer arranged on the anti-corrosion coating. The oxide layer is located in particular on an Al-based layer and preferably forms an outer end of the anti-corrosion coating.
[0122] The oxide layer consists in particular of more than 80% by weight of oxides, wherein the bulk of the oxides (i.e. more than 50% by weight of oxides) is aluminum oxide. In addition to aluminum oxide, the oxide layer optionally comprises hydroxides and / or magnesium oxide alone or a mixture thereof. The remainder of the oxide layer not occupied by oxides and optionally present hydroxides preferably consists of silicon, aluminum, iron and / or magnesium in metallic form. For optional embodiments with zinc as a component of the Al-based layer, the zinc oxide component is also present in the oxide layer.
[0123] The oxide layer of the flat steel product preferably has a thickness of more than 50 nm. In particular, the thickness of the oxide layer does not exceed 500 nm.
[0124] In an alternative configuration, the flat steel product comprises a zinc-based anti-corrosion coating. The anti-corrosion coating may have been applied on one or both sides of the flat steel product. "Both sides of the flat steel product" refers to the two opposite large faces of the flat steel product. The narrow faces are referred to as edges.
[0125] This zinc-based anticorrosion coating preferably comprises 0.2 wt %-6.0 wt % Al, 0.1 wt %-10.0 wt % Mg, optionally 0.1 wt %-40 wt % manganese or copper, optionally 0.1 wt %-10.0 wt % cerium, optionally no more than 0.2 wt % other elements, unavoidable impurities, and the balance of zinc. In particular, the Al content does not exceed 2.0 wt %, preferably no more than 1.5 wt %. The Mg content is especially no more than 3.0 wt %, preferably no more than 1.0 wt %. The anticorrosion coating can be applied by hot dip coating or by physical vapor deposition or by electrolytic methods.
[0126] Furthermore, the yield point of particularly refined flat steel products has a continuous progression or is only slightly pronounced. In the context of this application, a continuous progression means that there is no pronounced yield point. A yield point with a continuous progression can also be referred to as a yield point Rp0.2. In this context, a slightly pronounced yield point is understood to mean a pronounced yield point in which the difference ΔRe between the upper yield point limit ReH and the lower yield point limit ReL does not exceed 50 MPa. Therefore:
[0127] ΔRe=(ReH-ReL)<50MPa, where ReH=upper limit of yield point, MPa; ReL=lower limit of yield point, unit is MPa.
[0128] The method for producing a hot-formed flat steel product with an anti-corrosion coating according to the present invention comprises the following steps:
[0129] a) providing a slab or thin slab consisting of steel consisting of iron and inevitable impurities, optionally one or more of the elements "Ce, La, Nb, Cr, Cu, Mo, Ni, Ca, W", and the following components (in wt%):
[0130] C: 0.06%-0.5%,
[0131] Si: 0.05%-0.6%,
[0132] Mn: 0.4%-3.0%,
[0133] Al: 0.06%-1.0%,
[0134] B: 0.0005%-0.01%,
[0135] V: 0.010%-0.50%,
[0136] P: ≤0.03%,
[0137] S: ≤0.02%,
[0138] N: ≤0.02%,
[0139] Sn: ≤0.03%,
[0140] As: ≤0.01%
[0141] One or more of the optional elements "Ce, La, Nb, Cr, Cu, Mo, Ni, Ca, W" have the following contents:
[0142] Ce+La: 0.01%-0.03%,
[0143] Ti: 0.0005%-0.10%,
[0144] Nb: 0.001%-0.2%,
[0145] Cr: 0.01%-1.0%,
[0146] Cu: 0.01%-0.2%,
[0147] Mo: 0.002%-0.3%,
[0148] Ni: 0.01%-0.5%,
[0149] Ca: 0.0005%-0.005%,
[0150] W: 0.001%-1.00%,
[0151] Alternatively, the steel is composed of iron and inevitable impurities, optionally one or more of the elements "Al, Nb, Cr, Cu, Mo, Ni, Ca, W", and the following components (in wt%):
[0152] C: 0.06%-0.5%,
[0153] Si: 0.05%-0.6%,
[0154] Mn: 0.4%-3.0%,
[0155] B: 0.0005%-0.01%,
[0156] V: 0.010%-0.50%,
[0157] P: ≤0.03%,
[0158] S: ≤0.02%,
[0159] N: ≤0.02%,
[0160] Sn: ≤0.03%,
[0161] As: ≤0.01%,
[0162] Ce+La: 0.01%-0.03%
[0163] The content of one or more of the optional elements "Al, Nb, Cr, Cu, Mo, Ni, Ca, W" is:
[0164] Al: ≤1.0%,
[0165] Ti: 0.0005%-0.10%,
[0166] Nb: 0.001%-0.2%,
[0167] Cr: 0.01%-1.0%,
[0168] Cu: 0.01%-0.2%,
[0169] Mo: 0.002%-0.3%,
[0170] Ni: 0.01%-0.5%,
[0171] Ca: 0.0005%-0.005%,
[0172] W: 0.001%-1.00%;
[0173] b) penetratingly heating the slab or thin slab at a temperature (T1) of 1100° C. to 1400° C.;
[0174] c) optionally, pre-rolling the through-heated slab or thin slab to obtain an intermediate product having an intermediate product temperature (T2) of 1000° C. to 1200° C.;
[0175] d) hot rolling to obtain a hot rolled flat steel product, wherein the final rolling temperature (T3) is 750° C. to 1000° C.;
[0176] e) optionally, coiling the hot rolled flat steel product, wherein the coiling temperature (T4) does not exceed 700° C.;
[0177] f) optionally, descaling the hot rolled flat steel product;
[0178] g) optionally, cold rolling the flat steel product, wherein the degree of cold rolling is at least 30%;
[0179] h) annealing the flat steel product at an annealing temperature (T5) of 650° C. to 900° C.;
[0180] i) cooling the flat steel product to an immersion temperature (T6) of 650° C. to 800° C., preferably 670° C. to 800° C.;
[0181] j) applying an anti-corrosion coating to the flat steel product cooled to the dipping temperature by hot dipping in a melt bath having a melt temperature (T7) of 660° C. to 800° C., preferably 680° C. to 740° C.;
[0182] k) Cooling the coated flat steel product to room temperature, wherein a first cooling period t in the temperature range of 600° C. to 450° C. MT The second cooling period t is greater than 10 s, in particular greater than 14 s, and is in the temperature range of 400° C. to 300° C. LT More than 8s, especially more than 12s;
[0183] 1) Optionally, the coated flat steel product is temper-rolled.
[0184] In step a), a semi-finished product of the composition of the alloy for flat steel products as defined in the present invention is provided. This can be a slab produced by conventional continuous slab casting or by continuous thin slab casting.
[0185] In step b), the semi-finished product is through-heated at a temperature (T1) of 1100° C. to 1400° C. If the semi-finished product is to be cooled after casting, the semi-finished product is first reheated to 1100° C. to 1400° C. for through-heating. In order to ensure good formability in the subsequent rolling process, the through-heating temperature should be at least 1100° C. The through-heating temperature should not exceed 1400° C. to avoid melt phase separation in the semi-finished product.
[0186] In an optional step c), the semi-finished product is pre-rolled to an intermediate product. Thin slabs are usually not subjected to any pre-rolling. If necessary, thick slabs to be rolled into hot-rolled strip can be pre-rolled. In this case, the temperature (T2) of the intermediate product at the end of the pre-rolling should be at least 1000°C, so that the intermediate product contains sufficient heat for the subsequent finishing step. However, high rolling temperatures also promote grain growth during the rolling operation, which has an adverse effect on the mechanical properties of the flat steel product. In order to minimize grain growth during the rolling operation, the temperature of the intermediate product at the end of the pre-rolling should not exceed 1200°C.
[0187] In step d), the slab or thin slab is rolled, or if step c) has been carried out, the intermediate product is rolled to obtain a hot-rolled flat steel product. If step c) has been carried out, the intermediate product is usually finished rolled immediately after pre-rolling. Finishing rolling usually starts no later than 90 seconds after the end of pre-rolling. The slab, thin slab or, if step c) has been carried out, the intermediate product is rolled to completion at the final rolling temperature (T3). The final rolling temperature, i.e. the temperature of the completely hot-rolled flat steel product at the end of the hot rolling operation, is 750°C-1000°C. In the case of a final rolling temperature below 750°C, the amount of free vanadium is reduced because relatively large amounts of vanadium carbides are precipitated. The vanadium carbides precipitated during the finishing rolling process are very large. They usually have an average grain size of more than 30 nm and are no longer dissolved during subsequent annealing processes, such as annealing processes carried out before hot dip coating. The final rolling temperature is limited to a value not exceeding 1000°C to prevent coarsening of the austenite grains. Furthermore, a final rolling temperature of not more than 1000° C. is relevant for process-related purposes in order to establish a coiling temperature ( T4 ) of less than 700° C.
[0188] The hot rolling of the flat steel product can be carried out in the form of a continuous strip hot rolling operation or a reverse rolling operation. In the case of continuous strip hot rolling, step e) provides for the optional coiling of the hot-rolled flat steel product. To this end, the hot-rolled strip after hot rolling is cooled to the coiling temperature (T4) in less than 50 seconds. The cooling medium used for this purpose can be, for example, water, air or a combination of the two. The coiling temperature (T4) should not be greater than 700°C to avoid the formation of large vanadium carbides. There is no lower limit to the coiling temperature in principle. However, it has been found that a coiling temperature of at least 500°C is beneficial to cold rolling properties. Subsequently, the coiled hot-rolled strip is cooled to room temperature in air in a conventional manner.
[0189] In step f), the hot-rolled flat steel product is optionally derusted in a conventional manner by pickling or by another suitable treatment.
[0190] Prior to the annealing treatment in step g), the derusted hot-rolled flat steel product can optionally be subjected to cold rolling, for example in order to meet higher requirements on the thickness tolerance of the flat steel product. The degree of cold rolling (DCR) should be at least 30% in order to introduce sufficient deformation energy into the flat steel product for rapid recrystallization. The degree of cold rolling DCR is understood to mean the quotient of the cold-rolled thickness reduction ΔdCR divided by the hot-rolled strip thickness d:
[0191] DCR=ΔdCR / d
[0192] Where ΔdCR = thickness reduction during cold rolling in mm, d = hot rolled strip thickness in mm, where the thickness reduction ΔdCR is calculated based on the difference in thickness of the flat steel product before cold rolling relative to the thickness of the flat steel product after cold rolling. The flat steel product before cold rolling is usually a hot rolled strip with a hot rolled strip thickness d. The flat steel product after cold rolling is also often referred to as a cold rolled strip. The degree of cold rolling can in principle take very high values of more than 90%. However, it has been found that a degree of cold rolling of no more than 80% is advantageous for avoiding strip cracks.
[0193] In step h), the flat steel product is annealed at an annealing temperature (T5) of 650° C. to 900° C. For this purpose, the flat steel product is first heated to the annealing temperature within 10 to 120 seconds and then kept at the annealing temperature for 30 to 600 seconds. The annealing temperature is at least 650° C., preferably at least 720° C. Annealing temperatures above 900° C. are undesirable for economic reasons.
[0194] In step i), the annealed flat steel product is cooled to an immersion temperature (T6) in order to prepare it for the subsequent coating process. The immersion temperature is lower than the annealing temperature and is matched to the temperature of the melt pool. The immersion temperature is 600° C.-800° C., preferably at least 650° C., more preferably at least 670° C., more preferably up to 700° C. For a particularly uniform interface layer formation, it is important to have sufficient thermal energy in the interface layer between the steel substrate and the aluminum melt. This is not the case at temperatures below 600° C., so that unwanted compounds may form, whose subsequent reconversion may lead to pores. Above the preferred immersion temperature, the diffusion rate of iron into aluminum increases significantly, so that even at the beginning of the coating process, more iron can diffuse into the still liquid interface layer. The duration of the cooling of the annealed flat steel product from the annealing temperature T5 to the immersion temperature T6 is preferably 10-180 seconds. In particular, the immersion temperature T6 differs from the temperature of the melt pool T7 by no more than 30K, in particular no more than 20K, preferably no more than 10K.
[0195] In step j), the flat steel product is subjected to a coating treatment. The coating treatment is preferably achieved by continuous hot dip coating. The coating can be applied only on one side, on both sides or on all sides of the flat steel product. The coating treatment is preferably carried out as a hot dip coating process, in particular as a continuous process. The flat steel product is usually in contact with the melt pool on all sides so that it is coated on all sides. The melt pool containing the alloy applied to the flat steel product in liquid form is usually at a temperature (T7) of 660° C. to 800° C., preferably 680° C. to 740° C. It has been found that aluminum-based alloys are particularly suitable for coating aging-resistant flat steel products with anti-corrosion coatings. In this case, the melt pool contains 0.1% to 15% by weight of Si (preferably more than 1.0% by weight of Si), optionally 2% to 4% by weight of Fe, optionally up to 5% by weight of alkali metals or alkaline earth metals (preferably up to 1.0% by weight of alkali metals or alkaline earth metals), and optionally up to 15% by weight of Zn (especially up to 10% by weight of Zn), and optionally other components whose contents are limited to not more than 2.0% by weight in total, the remainder being aluminum. In a preferred variant, the Si content of the melt is 1.0% to 3.5% by weight or 7% to 12% by weight, in particular 8% to 10% by weight. In a preferred variant, the optional alkali metal or alkaline earth metal content in the melt contains 0.1% to 1.0% by weight of Mg, in particular 0.1% to 0.7% by weight of Mg, preferably 0.1% to 0.5% by weight of Mg. Furthermore, the optional alkali metal or alkaline earth metal content in the melt can comprise, in particular, at least 0.0015% by weight of Ca, in particular at least 0.01% by weight of Ca.
[0196] After the coating process, the coated flat steel product is cooled to room temperature in step k). The first cooling period t in the temperature range between 600° C. and 450° C. (medium temperature range MT) MT The second cooling period t is greater than 5 s, preferably greater than 10 s, and in particular greater than 14 s, and in the temperature range between 400° C. and 300° C. (low temperature range LT) LT Greater than 4 s, preferably greater than 8 s, in particular greater than 12 s.
[0197] The first cooling period t in the temperature range between 600°C and 450°C (medium temperature range MT) MT This can be achieved by gradual, continuous cooling or by holding the temperature for a certain period of time in this temperature range. Intermediate heating can even be carried out. It is important that the flat steel product is kept at least for a certain period of time during the cooling period t MTThe temperature range of the aluminum substrate is kept between 600°C and 450°C for a period of time. In this temperature range, on the one hand, there is a significant diffusion rate of iron into aluminum, and on the other hand, since the temperature is lower than half of the melting temperature of steel, the diffusion of aluminum into steel is inhibited. This allows iron to diffuse into the anti-corrosion coating, while aluminum does not diffuse significantly into the steel substrate.
[0198] Diffusion of iron into the corrosion protection coating has several advantages.
[0199] Firstly, the melting of the corrosion protection coating is delayed during austenitization before press hardening. Secondly, the thermal expansion coefficients of the corrosion protection coating and the substrate are homogenized. This means that the transition zone between the thermal expansion coefficients of the substrate and the surface becomes wider, which reduces thermal stresses during reheating.
[0200] At the same time, the diffusion of aluminum into the steel substrate has significant disadvantages. Due to the very high affinity of aluminum for nitrogen, a high aluminum content can have the effect of removing nitrogen from fine precipitates such as vanadium carbonitride, niobium carbonitride or titanium carbonitride, and instead preferentially forms coarse precipitates such as aluminum nitride at the grain boundaries. This deteriorates the collision performance and also reduces the bending angle. In addition, this destabilizes the fine precipitates (e.g., V- or Nb-containing precipitates) in the uppermost region of the substrate, which are important for many preferred properties. In addition, the uneven diffusion rate of aluminum in the steel substrate into ferrite compared to pearlite / bainite / martensite will lead to an uneven distribution of Al in the edge layer of the steel substrate. In order to improve the collision performance and bending performance, this situation should also be avoided. Therefore, these disadvantages of aluminum diffusion into the steel substrate are reduced or avoided by inhibition.
[0201] With the preferred first cooling time t MT (14s), the iron concentration in the interfacial transition layer increases to such an extent that the activity of the aluminum in the coating directly at the substrate boundary is further reduced. This then leads to an even further reduction in the absorption of aluminum into the substrate during austenitization before press hardening, with the associated advantages mentioned above.
[0202] The second cooling period t in the temperature range between 400°C and 300°C (low temperature range LT) LT This can also be achieved by gradual, continuous cooling or by holding the temperature for a certain period of time in this temperature range. Intermediate heating can even be carried out. It is important that the flat steel product is kept at least for a certain period of time during the cooling cycle t LT The temperature is maintained in the range of 400°C-300°C for a period of time.
[0203] In this temperature range, carbon still has a certain diffusion rate inside the steel matrix, while the thermodynamic solubility is very low. Therefore, carbon diffuses into and collects at lattice defects, such as dissolved V or Nb atoms. These atoms widen the atomic lattice due to their much higher atomic volume, thus increasing the size of the tetrahedral and octahedral interstices in the atomic lattice, so that the local solubility of C increases. This leads to clusters of C and V and / or Nb, which are subsequently transformed into very fine precipitates during the austenitizing step and / or transfer step of hot forming. These firstly lead to a refined austenite structure and secondly constitute hydrogen traps, resulting in a reduction in the free hydrogen content.
[0204] In the preferred case of holding times of more than 12 seconds, very fine iron carbides (called transition carbides) are additionally formed, which in turn dissolve very quickly during austenitization and lead to additional austenite grains, thus to an even finer austenite structure and thus also to a hardened structure.
[0205] The coated flat steel product may optionally be subjected to a temper rolling operation with a temper rolling degree of up to 2% in order to improve the surface roughness of the flat steel product.
[0206] The invention also relates to a metal profiled sheet metal component formed from a flat steel product, comprising the above-described steel substrate.
[0207] In particular, the metal profiled sheet part further comprises an anti-corrosion coating. The anti-corrosion coating has the advantage of preventing scale formation during austenitization in the hot forming operation. Furthermore, such an anti-corrosion coating protects the formed metal profiled sheet part from corrosion.
[0208] In one embodiment, the metal formed sheet component preferably comprises an aluminum-based anti-corrosion coating. The anti-corrosion coating of the metal formed sheet component preferably comprises an alloy layer and an Al-based layer. In the metal formed sheet component, the alloy layer is often also referred to as an interdiffusion layer.
[0209] The thickness of the anti-corrosion coating is preferably at least 10 μm, more preferably at least 20 μm, in particular at least 30 μm.
[0210] The thickness of the alloy layer is preferably less than 30 μm, more preferably less than 20 μm, in particular less than 16 μm, more preferably less than 12 μm. The thickness of the Al-based layer is determined by the difference in thickness between the anticorrosion coating and the alloy layer.
[0211] Here, the alloy layer is located on the steel substrate and directly adjoins the steel substrate. The alloy layer of the metal profiled sheet metal part preferably consists of 35% to 90% by weight of Fe, 0.1% to 10% by weight of Si, optionally up to 0.5% by weight of Mg and optionally other components whose contents are limited to a total of not more than 2.0% by weight, and the remainder of aluminum. Due to the further diffusion of iron into the alloy layer, the proportions of Si and Mg are correspondingly lower than their corresponding proportions in the melt in the melt pool.
[0212] The alloy layer preferably has a ferritic structure.
[0213] The Al-based layer of the metal-formed sheet component is located above and directly adjacent to the alloy layer of the steel component. The Al-based layer of the steel component preferably consists of 35-55 wt% Fe, 0.4-10 wt% Si, optionally up to 0.5 wt% Mg, and optionally other components limited to a total content of not more than 2.0 wt% and the balance of aluminum.
[0214] The Al-based layer may have a uniform element distribution, wherein the local element content varies by no more than 10%. In contrast, a preferred variant of the Al-based layer has a low silicon phase and a silicon-rich phase. The low silicon phase here is a region where the average Si content is at least 20% less than the average Si content of the Al-based layer. The silicon-rich phase here is a region where the average Si content is at least 20% more than the average Si content of the Al-based layer.
[0215] In a preferred variant, the silicon-rich phase is located within the low-silicon phase. In particular, the silicon-rich phase forms at least a 40% continuous layer bounded by the low-silicon regions. In an alternative embodiment, the silicon-rich phase is arranged in the low-silicon phase in the form of islands.
[0216] In the context of this application, "in island form" refers to an arrangement in which discrete incoherent regions are surrounded by another material, ie there are "islands" of a particular material within another material.
[0217] In a preferred variant, the steel component comprises an oxide layer arranged on the anti-corrosion coating. The oxide layer is particularly located on the Al-based layer and preferably forms the outer end of the anti-corrosion coating.
[0218] The oxide layer of the steel component consists in particular of more than 80% by weight of oxides, wherein the majority of the oxides (i.e. more than 50% by weight of the oxides) are aluminum oxide. In addition to aluminum oxide, the oxide layer optionally comprises hydroxide and / or magnesium oxide alone or in a mixture thereof. The remainder of the oxide layer not occupied by oxides and optionally hydroxides preferably consists of silicon, aluminum, iron and / or magnesium in metallic form.
[0219] The oxide layer preferably has a thickness of at least 50 nm, in particular at least 100 nm. Furthermore, the thickness is not greater than 4 μm, in particular not greater than 2 μm.
[0220] In a particular configuration, the metal form sheet component includes a zinc-based anti-corrosion coating.
[0221] This zinc-based anticorrosion coating preferably contains preferably up to 80 wt % Fe, 0.2 wt %-6.0 wt % Al, 0.1 wt %-10.0 wt % Mg, optionally 0.1 wt %-40 wt % manganese or copper, optionally 0.1 wt %-10.0 wt % cerium, optionally no more than 0.2 wt % other elements, unavoidable impurities and the balance of zinc. In particular, the Al content does not exceed 2.0 wt %, preferably no more than 1.5 wt %. The Fe content produced by inward diffusion is preferably greater than 20 wt %, particularly greater than 30 wt %. In addition, the Fe content is particularly no more than 70 wt %, particularly no more than 60 wt %. The Mg content is particularly no more than 3.0 wt %, preferably no more than 1.0 wt %. The anticorrosion coating can be applied by hot dip coating or by physical vapor deposition or by electrolytic methods.
[0222] In certain refinements, the steel substrate of the metal profiled sheet metal component has a structure having at least partially more than 80% martensite and / or lower bainite, preferably at least partially more than 90% martensite and / or lower bainite, in particular at least partially more than 95% martensite and / or lower bainite, more preferably at least partially more than 98% martensite and / or lower bainite. "Martensite and / or lower bainite" means that the corresponding structural component consists of martensite or lower bainite or a mixture of martensite and / or lower bainite. In an even more specific refinement, the steel substrate of the metal profiled sheet metal component has a structure having at least partially more than 80% martensite, preferably at least partially more than 90% martensite, in particular at least partially more than 95% martensite, more preferably at least partially more than 98% martensite. In this context, "partially having" or "partially having" means that there is a region of the metal profiled sheet metal component having the structure. Furthermore, there can also be regions of the profiled metal sheet component which have different structures. The profiled metal sheet component thus has the structure in sections or regions.
[0223] With high martensite contents or lower bainite contents, very high tensile strengths and yield points can be achieved.
[0224] In an improved variant, the metal profiled sheet metal component at least partially has a yield point of at least 950 MPa, in particular at least 1100 MPa, in particular at least 1200 MPa, preferably at least 1300 MPa, preferably at least 1400 MPa.
[0225] In an improved variant, the metal profiled sheet metal part at least partially has a tensile strength of at least 1000 MPa, in particular at least 1100 MPa, preferably at least 1300 MPa, preferably at least 1400 MPa, in particular at least 1600 MPa, preferably at least 1700 MPa, in particular at least 1800 MPa.
[0226] In particular, the metal profiled sheet metal component at least partially has an elongation at break A50 of at least 3.5%, in particular at least 4%, in particular at least 4.5%, preferably at least 5%, more preferably at least 6%, in particular at least 6.5%.
[0227] Furthermore, in a preferred variant, the metal profiled sheet metal part can at least partially have a bending angle of at least 30°, in particular at least 40°, in particular at least 45°, preferably at least 47°, in particular at least 48°, more preferably at least 49°.
[0228] The bending angle depends specifically on the position of the bending axis. Usually, a distinction is made between bending angles transverse to the rolling direction (i.e., with the bending axis at right angles to the rolling direction) and bending angles longitudinal to the rolling direction (i.e., with the bending axis parallel to the rolling direction). If a metal-formed sheet metal part has a certain bending angle (e.g., at least 45°), this means in the context of the present application that the two bending angles (parallel to the rolling direction and at right angles to the rolling direction) satisfy a corresponding relationship. In other words, for example, both are at least 45°.
[0229] In this context, "partially having" or "partially having" means that there are regions of the metal profiled sheet metal component having the stated mechanical properties. Furthermore, there may also be regions of the metal profiled sheet metal component having mechanical properties below the limit. Thus, the metal profiled sheet metal component has the stated mechanical properties in sections or regions. This is because different regions of the metal profiled sheet metal component can be subjected to different heat treatments. For example, individual regions can be cooled faster than other regions, with the result that, for example, more martensite is formed in the faster cooling region. Thus, different mechanical properties are also established in different regions.
[0230] The above-mentioned mechanical criteria have been found to be particularly advantageous in order to ensure use in motor vehicles with good crash performance.
[0231] In certain developments, the metal formed sheet metal component has fine precipitates in the structure, in particular in the form of vanadium carbonitrides, niobium carbonitrides and / or titanium carbonitrides.
[0232] In the context of this application, fine precipitates are understood to mean all precipitates with a diameter of less than 30 nm. Other precipitates are referred to as coarse precipitates.
[0233] In a preferred embodiment, the average diameter of the fine precipitates is not greater than 11 nm, preferably not greater than 10 nm, in particular not greater than 8 nm, preferably not greater than 6 nm.
[0234] In a further preferred embodiment, the metal profiled sheet metal component has a large number of fine precipitates in the structure. In the context of the present application, a large number of fine precipitates means that more than 80%, preferably more than 90% of all precipitates are fine precipitates. This means that more than 80%, preferably more than 90% of all precipitates have a diameter of less than 30 nm.
[0235] Fine precipitates lead to a particularly fine structure with small particle sizes. As a result, the fine structure is more homogeneous. Improvements in mechanical properties are seen, in particular lower crack sensitivity, thus improved bending properties and higher elongation at break. This also leads to better toughness and more pronounced fracture necking characteristics.
[0236] The true mechanical indicators of the metal-formed sheet metal part are determined by first subjecting the metal-formed sheet metal part to cathodic coating or a similar heat treatment with dip paint. In the automotive industry, the corresponding parts are usually subjected to a cathodic electrophoretic coating operation. In cathodic dip coating, the parts are first coated in an aqueous solution. The coating is then baked in a heat treatment. This involves heating the metal-formed sheet metal part to 170°C and keeping it at this temperature for 20 minutes. Subsequently, the part is cooled to room temperature under ambient air. Since this heat treatment can affect the mechanical indicators, in the context of this application, the mechanical indicators (yield point, tensile strength, yield point ratio, elongation at break A50, bending angle, Vickers hardness) should be regarded as being present in a part with a cathodic dip coating or in a part subjected to a heat treatment similar to cathodic dip coating after formation. In practice, the heat treatment of the cathodic dip coating is slightly different. The conventional temperature is 165°C-180°C and the holding time is 12-30 minutes. However, the changes in mechanical properties due to these changes (165°C–180°C; 12–30 min) were negligible in the subsequent heat treatments.
[0237] In a preferred variant, the metal profiled sheet metal component comprises a cathodic dip coating.
[0238] An improved variant of the metal formed sheet metal component is characterized in that the anti-corrosion coating is an aluminum-based anti-corrosion coating and in that the metal formed sheet metal component comprises an alloy layer and an Al-based layer.
[0239] In a preferred embodiment, the metal profiled sheet metal component has a fracture stress of more than 610 MPa, in particular more than 625 MPa, in a modified slow strain rate test. This test ensures that the preferred embodiment is less hydrogen sensitive. In practical use of the metal profiled sheet metal component, this has the effect of reducing the risk of hydrogen embrittlement.
[0240] The metal profiled sheet component of the present invention is preferably a component for a land vehicle, a sea vessel or an aircraft. It is more preferably an automobile component, especially a body component. The component is preferably a B-pillar, a longitudinal beam, an A-pillar, a sill beam or a cross beam.
[0241] In the method according to the invention for producing a metal profiled sheet metal part according to the invention of the type described above, at least the following steps are carried out:
[0242] a) providing a sheet metal blank made of the above flat steel product, in particular a flat steel product comprising a steel substrate, the steel consisting of iron and unavoidable impurities, optionally one or more of the elements “Ce, La, Nb, Cr, Cu, Mo, Ni, Ca, W”, and the following components (in wt. %):
[0243] C: 0.06%-0.5%,
[0244] Si: 0.05%-0.6%,
[0245] Mn: 0.4%-3.0%,
[0246] Al: 0.06%-1.0%,
[0247] B: 0.0005%-0.01%,
[0248] V: 0.010%-0.50%,
[0249] P: ≤0.03%,
[0250] S: ≤0.02%,
[0251] N: ≤0.02%,
[0252] Sn: ≤0.03%,
[0253] As: ≤0.01%
[0254] One or more of the optional elements "Ce, La, Nb, Cr, Cu, Mo, Ni, Ca, W" have the following contents:
[0255] Ce+La: 0.01%-0.03%,
[0256] Ti: 0.0005%-0.10%,
[0257] Nb: 0.001%-0.2%,
[0258] Cr: 0.01%-1.0%,
[0259] Cu: 0.01%-0.2%,
[0260] Mo: 0.002%-0.3%,
[0261] Ni: 0.01%-0.5%,
[0262] Ca: 0.0005%-0.005%,
[0263] W: 0.001%-1.00%.
[0264] Alternatively, the steel is composed of iron and inevitable impurities, the following components, optionally one or more of the elements "Al, Nb, Cr, Cu, Mo, Ni, Ca, W", and the following components (in wt%):
[0265] C: 0.06%-0.5%,
[0266] Si: 0.05%-0.6%,
[0267] Mn: 0.4%-3.0%,
[0268] B: 0.0005%-0.01%,
[0269] V: 0.010%-0.50%,
[0270] P: ≤0.03%,
[0271] S: ≤0.02%,
[0272] N: ≤0.02%,
[0273] Sn: ≤0.03%,
[0274] As: ≤0.01%,
[0275] Ce+La: 0.01%-0.03%
[0276] The content of one or more of the optional elements "Al, Nb, Cr, Cu, Mo, Ni, Ca, W" is:
[0277] Al: ≤1.0%,
[0278] Ti: 0.0005%-0.10%,
[0279] Nb: 0.001%-0.2%,
[0280] Cr: 0.01%-1.0%,
[0281] Cu: 0.01%-0.2%,
[0282] Mo: 0.002%-0.3%,
[0283] Ni: 0.01%-0.5%,
[0284] Ca: 0.0005%-0.005%,
[0285] W: 0.001%-1.00%;
[0286] b) heating the sheet metal blank so that the AC3 temperature of the blank is at least to a certain extent exceeded and the temperature T of the blank when inserted into a forming tool provided for the hot press forming operation (step c)) is ins at least partially at a temperature above Ms+100° C., in particular above Ms+300° C., wherein Ms denotes the martensite start temperature;
[0287] c) Inserting the heated sheet metal blank into the forming tool, wherein the transfer time t required for removing the blank from the heating device and inserting the blank is trans No more than 20s, preferably no more than 15s;
[0288] d) hot pressing the sheet metal blank to obtain a metal formed sheet metal part, wherein the blank is cooled during the hot pressing process at a cooling rate r at least partially greater than 30 K / s. tool In a period greater than 1s tool Internal cooling to target temperature T target , and optionally maintained at that temperature;
[0289] e) Removing the metal formed sheet part from the tool after it has cooled to the target temperature.
[0290] In the method of the invention, a slab consisting of a steel of a suitable composition as described above is thus provided (step a)), which is then heated in a manner known per se, so that the AC3 temperature of the slab is at least partially exceeded and the temperature of the slab when inserted into a forming tool provided for a hot press forming operation (step c)) is at least partially at a temperature above Ms+100°C, in particular above Ms+300°C. In particular, the temperature of the slab when inserted is at least partially 600°C. In a particularly preferred variant, the temperature of the slab when inserted is at least partially, in particular completely, in the range of 600°C-850°C, in order to ensure good formability and sufficient hardenability. In the context of the present application, "partially exceeding the temperature" (here AC3 or Ms+100°C) means that at least 30%, in particular at least 60% of the volume of the slab (preferably the entire slab) exceeds the corresponding temperature. The same applies to the presence of a temperature in the interval of 600°C-850°C at least partially in the preferred variants described above. At least 30% of the slab thus has an austenitic structure when inserted into the forming tool, which means that the transition from ferrite to austenite structure does not have to be completed when inserted into the forming tool. On the contrary, up to 70% of the volume of the slab can be composed of other structural components, such as annealed bainite, annealed martensite and / or unrecrystallized or partially recrystallized ferrite when inserted into the forming tool. For this reason, specific areas of the slab can be kept at a lower temperature level than other areas during heating. For this purpose, the supply of heat can be directed only specifically to specific areas of the slab, or the supply of heat can be shielded for the parts to be heated to a lesser extent. In the parts where the temperature of the slab material is kept low, only a significantly smaller amount of martensite or lower bainite (if any) is formed during the forming process in the tool, so that the structure there is much softer than in the corresponding other parts where the martensitic structure (or the structure containing lower bainite) is present. In this way, softer regions can be specifically established in the correspondingly formed sheet metal component, in which, for example, the toughness is optimal for the corresponding end use, while other regions of the sheet metal component have maximized strength.
[0291] The maximum strength properties of the resulting sheet metal part can be achieved by achieving at least a certain temperature of Ac3 to 1000° C., preferably 850° C. to 950° C., in the sheet metal blank.
[0292] The minimum temperature Ac3 to be exceeded is determined by the formula specified by HOUGARDY, HP in the following: HOUGARDY, HP, Werkstoffkunde Stahl, Band 1: Grundlagen [Material Science, Steel, Volume 1: Principles], Verlag Stahleisen GmbH, Düsseldorf, 1984, p. 229:
[0293] AC3[℃]=(902wt%-225*%C+19*%Si-11*%Mn-5*%Cr+13*%Mo-20*%Ni+55*%V)[℃ / wt%]
[0294] Among them, %C = the corresponding C content of the steel constituting the slab, %Si = the corresponding Si content of the steel constituting the slab, %Mn = the corresponding Mn content of the steel constituting the slab, %Cr = the corresponding Cr content of the steel constituting the slab, %Mo = the corresponding Mo content of the steel constituting the slab, %Ni = the corresponding Ni content of the steel constituting the slab, and %V = the corresponding V content of the steel constituting the slab.
[0295] By completely penetrating the heated plate blank in step b), an optimally uniform distribution of the properties can be achieved.
[0296] In a preferred embodiment, the average heating rate r of the sheet metal blank during heating in step b) is furnace is at least 3 K / s, preferably at least 5 K / s, in particular at least 6 K / s, preferably at least 8 K / s, in particular at least 10 K / s, preferably at least 15 K / s. The average heating rate r furnace is the average heating rate from 30°C to 700°C.
[0297] In a preferred embodiment, the normalized average heating θ norm It is at least 5 Kmm / s, in particular at least 8 Kmm / s, preferably at least 10 Kmm / s. The normalized average heating is at most 15 Kmm / s, in particular at most 14 Kmm / s, preferably at most 13 Kmm / s.
[0298] Average heating Θ means the product of the average heating rate from 30°C to 700°C (unit: Kelvin / second (K / s)) and the sheet thickness (unit: millimeter (mm)).
[0299] For normalized average heating, the product Θ is calculated by the current furnace temperature T furnace Relative to the reference furnace temperature T furnace,参考 900°C (=1173.15K) is normalized as follows:
[0300]
[0301] The furnace temperature shall in each case be given in Kelvin (K).
[0302] In a preferred embodiment, the heating is carried out at a furnace temperature T of at least Ac3+10°C, preferably at least 850°C, preferably at least 880°C, more preferably at least 900°C, in particular at least 920°C, and not more than 1000°C, preferably not more than 950°C, more preferably not more than 930°C. furnace is implemented in .
[0303] Preferably, the dew point of the furnace atmosphere in the furnace here is at least -20°C, preferably at least -15°C, especially at least -5°C, more preferably at least 0°C, and not more than +25°C, preferably not more than +20°C, especially not more than +15°C.
[0304] In a specific embodiment, the heating in step b) is carried out in steps in zones with different temperatures. In particular, the heating is carried out in a roller hearth furnace with different heating zones. Here, the heating is carried out in a first heating zone with a temperature (referred to as the furnace inlet temperature) of at least 650° C., preferably at least 680° C., in particular at least 720° C. The temperature in the first heating zone is preferably not more than 900° C., in particular not more than 850° C. Further preferably, the maximum temperature of all heating zones in the furnace does not exceed 1200° C., in particular does not exceed 1000° C., preferably does not exceed 950° C., and more preferably does not exceed 930° C.
[0305] In both variants (constant furnace temperature, stepped heating), the total time in the furnace, t, consisting of the heating time and the holding time furnace Preferably at least 2 minutes, in particular at least 3 minutes, preferably at least 4 minutes. Furthermore, in both variants, the total time in the furnace is preferably not more than 20 minutes, in particular not more than 15 minutes, preferably not more than 12 minutes, in particular not more than 8 minutes. A longer total time in the furnace has the advantage of ensuring uniform austenitization of the sheet metal blank. On the other hand, too long a stay above Ac3 can lead to grain coarsening, which has an adverse effect on the mechanical properties.
[0306] The blank heated in this way is taken out of a corresponding heating device, which can be, for example, a conventional heating furnace, an induction heating device known per se, or a conventional device for keeping steel parts heated, and is conveyed to the forming tool at a sufficient speed so that its temperature when it reaches the tool is at least partially higher than Ms+100°C, in particular higher than Ms+300°C, preferably higher than 600°C, in particular higher than 650°C, and more preferably higher than 700°C. Ms here represents the martensite starting temperature. In particularly preferred variants, the temperature is at least partially higher than the AC1 temperature. In all these variants, the temperature does not exceed 900°C in particular. These temperature ranges ensure good formability of the material as a whole.
[0307] In step c), the transfer of the austenitized blank from the correspondingly used heating device to the forming tool is preferably carried out within no more than 20 seconds, in particular no more than 15 seconds. This rapid transport is required to avoid excessive cooling before forming.
[0308] The tool when inserting the blank is usually at a temperature of between room temperature (RT) and 200° C., preferably between 20° C. and 180° C., in particular between 50° C. and 150° C. If, for example, the cooling water used is slightly colder (for example 15° C.), the temperature of the tool when inserting the blank can also be slightly below room temperature. This means that when inserting the blank, the temperature of the tool in the various embodiments is between 10° C. and 200° C. In a particular embodiment, the tool can be adjusted to a temperature T of at least 200° C., in particular at least 300° C., at least in the region T tool , in order to only partially harden the component. In addition, the tool temperature T tool It is preferably not more than 600° C., in particular not more than 550° C. It is only necessary to ensure that the tool temperature T tool Lower than the desired target temperature T target The residence time in the tool is t tool Preferably it is at least 2 s, especially at least 3 s, more preferably at least 5 s. The residence time in the tool is preferably not more than 25 s, especially not more than 20 s, preferably not more than 10 s.
[0309] Target temperature T of the metal forming sheet part target At least to some extent below 400° C., preferably below 300° C., especially below 250° C., preferably below 200° C., more preferably below 180° C., in particular below 150° C. Alternatively, the target temperature T of the metal profiled sheet part target More preferably it is below Ms-50°C, wherein Ms represents the martensite start temperature. Furthermore, the target temperature of the metal formed sheet part is preferably at least 20°C, more preferably at least 50°C.
[0310] The martensite starting temperature of steel within the specified range of the present invention should be calculated by the following formula:
[0311] Ms[℃]=(490.85wt%-302.6%C-30.6%Mn-16.6%Ni-8.9%Cr+2.4%Mo-11.3%Cu+8.58%Co+7.4%W-14.5%Si)[℃ / wt%]
[0312] Here, %C represents the C content of the corresponding steel, %Mn represents the Mn content of the corresponding steel, %Mo represents the Mo content of the corresponding steel, %Cr represents the Cr content of the corresponding steel, %Ni represents the Ni content of the corresponding steel, %Cu represents the Cu content of the corresponding steel, %Co represents the Co content of the corresponding steel, %W represents the W content of the corresponding steel, and %Si represents the Si content of the corresponding steel, the unit is weight %.
[0313] The AC1 temperature and AC3 temperature of the steel within the scope of the present invention shall be calculated by the following formula:
[0314] AC1[°C]=(739 wt%-22*%C-7*%Mn+2*%Si+14*%Cr+13*%Mo-13*%Ni+20*%V)[°C / wt%]
[0315] AC3[℃]=(902wt%-225*%C+19*%Si-11*%Mn-5*%Cr+13*%Mo-20*%Ni+55*%V)[℃ / wt%]
[0316] Among them, %C represents the C content of the corresponding steel, %Si represents the Si content of the corresponding steel, %Mn represents the Mn content of the corresponding steel, %Cr represents the Cr content of the corresponding steel, %Mo represents the Mo content of the corresponding steel, %Ni represents the Ni content of the corresponding steel, and %V represents the vanadium content of the corresponding steel (Brandis H 1975TEW-Techn. Ber. 1 8 10).
[0317] Thus, in the tool, the blank is not only formed to obtain a metal-formed sheet metal part, but is also simultaneously quenched to the target temperature. The cooling rate to the target temperature in the tool is r tool In particular, at least 20 K / s, preferably at least 30 K / s, in particular at least 50 K / s, in a specific embodiment at least 100 K / s.
[0318] After the metal sheet component is removed in step e), a cooling period T of 0.5-600 seconds is carried out. AB The metal forming sheet part is cooled to a cooling temperature T of less than 100°C. AB This is usually achieved by air cooling.
[0319] In a preferred embodiment variant, the flat steel product and the method for producing a profiled metal sheet component are developed in such a way that the flat steel product has regions of different thicknesses. The profiled metal sheet component is likewise developed in such a way that it has regions of different thicknesses.
[0320] Areas of different thicknesses in flat steel products (called "tailored blanks") can be produced in various ways:
[0321] - Special cold rolling passes in which individual areas are rolled more vigorously or more frequently (eg up to 50% rolling degree) lead to lower material thickness in these areas and thus to lower thickness (so-called "tailored rolled blanks").
[0322] - Sheet metal blanks of different thicknesses are joined to one another by welding (usually by laser welding) in order to achieve a coherent sheet metal blank having areas of different thicknesses (so-called "tailor-made welded blank").
[0323] - The patch is applied to the existing sheet metal blank to thicken the area by resistance spot welding or laser welding. Alternatively, the patch can be applied by structural adhesive.
[0324] By means of the described method for producing a profiled sheet metal component, a flat steel product having regions of different thicknesses results in a profiled sheet metal component having regions of different thicknesses.
[0325] Areas of different thickness have the advantage that individual areas of the final metal-formed sheet metal component can be specifically reinforced. In this way, those components that are subject to abnormal stresses (e.g. during a crash) can be provided with a correspondingly stable construction, while other components have a thinner construction in order to reduce the weight of the component. Thus, a weight-optimized component is produced with specific reinforcement in highly stressed areas.
[0326] In a preferred embodiment variant, the flat steel product and the method for producing a profiled metal sheet component are developed in such a way that the flat steel product has regions of different materials. The profiled metal sheet component is likewise developed in such a way that it has regions of different materials.
[0327] By welding (usually by laser welding), sheet metal blanks made of different materials can also be joined to one another to achieve a coherent sheet metal part with regions of different strengths. This is also often covered under the umbrella term "custom welded blank". This achieves the effect that there are sections of the sheet metal part with good formability and relatively low strength, while there are other sections with high strength.
[0328] Of course, the aforementioned options for locally individually adjusting the properties of the profiled sheet metal parts can also be combined.
[0329] In a preferred embodiment, the produced metal sheet metal parts can be used in vehicle construction, for example as a whole or as part of a metal sheet metal part, for example as B-pillars, A-pillars, floor beams, roof frames, bumper beams, door reinforcements, underbody protection for battery cells, etc.
[0330] The invention is illustrated in detail by means of working examples.
[0331] Figure 1Shown is the sample geometry when measuring hydrogen embrittlement resistance by a modified slow strain rate test.
[0332] The effect of the present invention is shown by carrying out a number of experiments. For this purpose, slabs having the composition specified in Table 1 are produced, with a thickness of 200 mm-280 mm and a width of 1000 mm-1200 mm, heated to the corresponding temperature T1 in a push furnace and kept at T1 for 30 to 450 minutes until the core of the slab reaches the temperature T1, whereby the slab is penetrated heated. The production parameters are reported in Table 2. The slabs of the respective penetration heating temperature T1 are discharged from the push furnace and hot rolled. The experiments are carried out in the form of a continuous strip hot rolling operation. For this purpose, the slabs are first pre-rolled into an intermediate product with a thickness of 40 mm, and the intermediate products, which can also be referred to as pre-strips in the strip hot rolling operation, each have an intermediate product temperature T2 at the end of the pre-rolling stage. Immediately after the pre-rolling, the pre-strip is sent to the finishing rolling so that the intermediate product temperature T2 corresponds to the initial rolling temperature of the finishing rolling stage. The pre-strip is rolled into a hot strip with a final thickness of 3 mm to 7 mm and the corresponding final rolling temperature T3 specified in Table 2, cooled to the corresponding coiling temperature, and coiled into a coil at the corresponding coiling temperature T4 and then cooled in still air. Before cold rolling with the cold rolling degree specified in Table 2, the hot strip is derusted by pickling in a conventional manner. The cold-rolled flat steel products are heated to the respective annealing temperature T5 in a tunnel annealing furnace and kept at the annealing temperature for 100 s in each case and then cooled to the respective immersion temperature T6 at a cooling rate of 1 K / s. The cold strip with the respective immersion temperature T6 is passed through a melt coating bath at a temperature T7. The composition of the coating bath is reported in Table 3. After the coating operation, the coated strip is blown in a conventional manner to produce a specific layer thickness (see Table 3). The strip is first cooled to 600°C at an average cooling rate of 10 K / s to 15 K / s. During the further cooling process at 600℃-450℃ and 400℃-300℃, the strip is cooled for the cooling period T specified in Table 2. MT and T LT Cooling. The strip is cooled at 450° C.-400° C. and below 220° C., in each case at a cooling rate of 5 K / s-15 K / s.
[0333] Table 4 is a compilation of the combinations of steel variants (see Table 1) with process variants (see Table 2) and coatings (see Table 3).
[0334] Steel composition 1 is a reference example that does not conform to the present invention. Accordingly, experiments 1 and 5 do not conform to the present invention.
[0335] In all experiments, the thickness of the produced steel strip was 1.5 mm.
[0336] After cooling to room temperature, samples were taken from the cooled steel strip in the transverse direction of the rolling direction according to DIN EN ISO 6892-1 sample form 2 (Annex B, Table B1). The samples were subjected to tensile tests according to DIN EN ISO 6892-1 sample form 2 (Annex B, Table B1). Table 4 gives the results of the tensile tests. During the tensile test, the following material indices were determined: the type of yield point, which is represented by Re as a distinct yield point, by Rp as a continuous yield point, and in the case of a continuous yield point, the yield point value Rp0.2 was taken, in the case of a distinct yield point, the lower yield point ReL was taken, the upper yield point ReH was taken, and the difference ΔRe between the upper and lower yield points and the tensile strength Rm. All samples have a continuous yield point Rp, or only a slightly distinct yield point, and the difference ΔRe between the upper and lower yield points does not exceed 50 MPa. There is a continuous yield point for sample 6, and a distinct yield point for all other samples. Therefore, the yield point Rp0.2 of sample 6 is reported. For all other samples, the upper and lower limits of the yield point are reported.
[0337] From each of the eight strips thus produced, blanks were separated for further experiments. In these experiments, blanks with dimensions of 194 × 400 mm 2 The sheet metal forming sheet component samples 1-8 have been hot-pressed from the corresponding blanks to give the components in the form of contours. For this purpose, the blanks have been heated in a heating device, such as a conventional heating furnace, at a furnace temperature T furnace The furnace is heated from room temperature at an average heating rate of r furnace Heating (30°C to 700°C). The total duration in the furnace (including heating and holding) is designated as t furnace In all cases, the dew point of the furnace atmosphere was -5°C. Subsequently, the blank was removed from the heating device and heated at a temperature T tool The blank is inserted into the forming tool. When it is removed from the furnace, the blank has reached the furnace temperature. The transfer time t, which consists of the time for removal from the heating device, transfer to the tool and insertion into the tool, is trans In all cases, the temperature T of the blank when it is inserted into the forming tool is ins Above the corresponding martensite starting temperature of +100° C. The blank has been formed into a corresponding sheet metal part in a forming tool, which is cooled in the tool at a cooling rate r tool Cooling. The residence time in the tool is designated as t tool Finally, the sample was cooled to room temperature under air. Table 5 is a summary of these parameters, where "RT" is the abbreviation for room temperature.
[0338] The parameters used for the forming process here are such that the martensitic structure is essentially fully formed.
[0339] Table 6 is a compilation of the overall results obtained for the metal-formed sheet metal parts. The first column indicates the sample number, the steel type according to Table 1, the process variant according to Table 2, the coating according to Table 3 and the hot forming variant according to Table 5. The further columns give the yield point Rp, the tensile strength Rm and the elongation at break A50. These values were determined on samples taken transversely to the rolling direction on the flat surface of the contoured part according to DIN EN ISO 6892-1 sample form 2 (Annex B, Table B1). In addition, the bending angles transversely and longitudinally to the rolling direction are reported according to VDA standard 238-100. The bending angle determined here is calculated according to the path of the punch by the formula specified in the standard (the determined bending angle (also called the maximum bending angle) is the bending angle at which the force is maximum in the bending test).
[0340] All mechanical indices in Table 6 were determined using samples cut from a flat portion of the formed hat-shaped profile. In addition, the mechanical indices in Table 6 (except for the fracture stress in the modified slow strain rate test) were determined after the cathodic electrocoating was applied to the formed metal-formed sheet part. During the coating process, the metal-formed sheet part was heated to 170°C and maintained at this temperature for 20 minutes. Subsequently, the metal-formed sheet part was cooled to room temperature under ambient air.
[0341] The fracture stress in the modified slow strain rate test was found without any such cathodic electrocoating and without similar heat treatment.
[0342] In addition to the mechanical properties, it was determined that the structure was completely martensitic in all cases (i.e., more than 99% martensite). In addition, for samples 5, 6 and 8, the precipitates in the structure were determined to be in the form of vanadium carbonitrides, niobium carbonitrides and / or titanium carbonitrides. The precipitates were determined with the aid of electron images and X-ray images (TEM and EDX) using carbon extraction replicas. The carbon extraction replicas were made using longitudinal sections (20×30 mm). The resolution of the measurements was 10,000 to 200,000 times. These images can be used to divide the precipitates into coarse precipitates and fine precipitates. Fine precipitates refer to all precipitates with a diameter of less than 30 nm. Other precipitates are referred to as coarse precipitates. By simple counting, the proportion of fine precipitates in the total number of precipitates in the measuring area can be determined. In addition, for the fine precipitates, the average diameter was calculated by computer-assisted image analysis. For all three samples examined, the proportion of fine precipitates was greater than 90%. The average diameter of the fine precipitates of Sample 5 was 5 nm, the average diameter of Sample 6 was 14 nm, and the average diameter of Sample 8 was 4.5 nm.
[0343]
[0344]
[0345]
Claims
1. A flat steel product for thermoforming, comprising a steel substrate composed of steel, the steel consisting of iron and inevitable impurities, one or more of the optional elements "Ce, La, Nb, Cr, Cu, Mo, Ni, Ca, W", and the following components: C:0.06%-0.5%, Si: 0.05% - 0.6%, Mn: 0.4% - 3.0%, Al:0.06%-0.35%, B:0.0005%-0.01%, V:0.010%-0.50%, P:≤0.03%, S:≤0.02%, N:≤0.02%, Sn: ≤0.03%, As: ≤0.01%, The content of one or more of the optional elements "Ce, La, Nb, Cr, Cu, Mo, Ni, Ca, W" is: Ce + La: 0.01% - 0.03%, Ti: 0.0005% - 0.10%, Nb: 0.001% - 0.2%, Cr:0.01%-1.0%, Cu: 0.01% - 0.2%, Mo: 0.002% - 0.3%, Ni: 0.01% - 0.5%, Ca: 0.0005% - 0.005%, W:0.001%-1.00%, Alternatively, the steel consists of iron and inevitable impurities, one or more of the optional elements "Al, Nb, Cr, Cu, Mo, Ni, Ca, W", and the following components: C:0.06%-0.5%, Si: 0.05% - 0.6%, Mn: 0.4% - 3.0%, B:0.0005%-0.01%, V:0.010%-0.50%, P:≤0.03%, S:≤0.02%, N:≤0.02%, Sn: ≤0.03%, As: ≤0.01%, Ce + La: 0.01% - 0.03%, The content of one or more of the optional elements "Al, Nb, Cr, Cu, Mo, Ni, Ca, W" is: Al:≤1.0%, Ti: 0.0005% - 0.10%, Nb: 0.001% - 0.2%, Cr:0.01%-1.0%, Cu: 0.01% - 0.2%, Mo: 0.002% - 0.20%, Ni: 0.01% - 0.5%, Ca: 0.0005% - 0.005%, W:0.001%-1.00%。 2. The flat steel product according to claim 1, characterized in that The ratio of the Al content to the sum of the Nb and V contents, Al / (Nb + V), is: Al / (Nb + V) ≤ 30.
0.
3. The flat steel product according to claim 1 or 2, characterized in that The element contents satisfy the following conditions: 0.7 wt% < Mn + Cr < 3.5 wt%.
4. The flat steel product according to any one of the preceding claims, characterized in that The flat steel product has an anti-corrosion coating on at least one side.
5. The flat steel product according to claim 4, characterized in that The anti-corrosion coating is an aluminum-based anti-corrosion coating and has an alloy layer and an Al base layer.
6. The flat steel product according to claim 5, characterized in that The alloy layer consists of 35 wt% to 60 wt% of Fe, optional other components with a total content limited to no more than 5.0 wt%, and the balance of aluminum, and / or The Al base layer consists of 1.0 wt% to 15 wt% of Si, optional 2 wt% to 4 wt% of Fe, optional up to 5.0 wt% of alkali metals or alkaline earth metals, optional up to 10 wt% of Zn, optional other components with a total content limited to no more than 2.0 wt%, and the balance of aluminum.
7. The flat steel product according to any one of claims 1 to 6, characterized in that The flat steel product has a yield point (Rp0.2) with a continuous progression or a difference ΔRe between the upper yield point (ReH) and the lower yield point (ReL) not exceeding 50 MPa.
8. A production method of a flat steel product for thermoforming with an anti-corrosion coating, comprising the following steps: a) providing a slab or thin slab consisting of steel, which consists, in weight %, of iron and inevitable impurities, optionally one or more of the elements "Ce, La, Nb, Cr, Cu, Mo, Ni, Ca, W", and the following components: C:0.06%-0.5%, Si: 0.05%-0.6%, Mn: 0.4%-3.0%, Al:0.06%-0.35%, B:0.0005%-0.01%, V:0.010%-0.50%, P:≤0.03%, S:≤0.02%, N:≤0.02%, Sn: ≤0.03%, As: ≤0.01%, The content of one or more of the optional elements "Ce, La, Nb, Cr, Cu, Mo, Ni, Ca, W" is: Ce+La: 0.01%-0.03%, Ti: 0.0005%-0.10%, Nb: 0.001%-0.2%, Cr:0.01%-1.0%, Cu: 0.01%-0.2%, Mo: 0.002%-0.3%, Ni: 0.01%-0.5%, Ca: 0.0005%-0.005%, W:0.001%-1.00%, Alternatively, the steel is composed of iron and inevitable impurities, optionally one or more of the elements "Al, Nb, Cr, Cu, Mo, Ni, Ca, W", and the following components in weight %: C:0.06%-0.5%, Si: 0.05%-0.6%, Mn: 0.4%-3.0%, B:0.0005%-0.01%, V:0.010%-0.50%, P:≤0.03%, S:≤0.02%, N:≤0.02%, Sn: ≤0.03%, As: ≤0.01%, Ce+La: 0.01%-0.03%, The content of one or more of the optional elements "Al, Nb, Cr, Cu, Mo, Ni, Ca, W" is: Al:≤1.0%, Ti: 0.0005%-0.10%, Nb: 0.001%-0.2%, Cr:0.01%-1.0%, Cu: 0.01%-0.2%, Mo: 0.002%-0.20%, Ni: 0.01%-0.5%, Ca: 0.0005%-0.005%, W:0.001%-1.00%; b) penetratingly heating the slab or thin slab at a temperature (T1) of 1100° C. to 1400° C.; c) optionally, pre-rolling the through-heated slab or thin slab to obtain an intermediate product having an intermediate product temperature (T2) of 1000° C. to 1200° C.; d) hot rolling to obtain a hot rolled flat steel product, wherein the final rolling temperature (T3) is 750° C. to 1000° C.; e) optionally, coiling the hot rolled flat steel product, wherein the coiling temperature (T4) does not exceed 700° C.; f) removing rust from the hot rolled flat steel product; g) optionally, cold rolling the flat steel product, wherein the degree of cold rolling is at least 30%; h) annealing the flat steel product at an annealing temperature (T5) of 650° C. to 900° C.; i) cooling the flat steel product to an immersion temperature (T6) of 650° C. to 800° C., preferably 670° C. to 800° C.; j) applying the anti-corrosion coating to the flat steel product cooled to the dipping temperature by hot dipping in a melt bath having a melt temperature (T7) of 660° C. to 800° C., preferably 670° C. to 740° C.; k) Cooling the coated flat steel product to room temperature, wherein a first cooling period t in the temperature range of 600° C. to 450° C. MT The second cooling period t is greater than 5 s, preferably greater than 10 s, in particular greater than 14 s, and is in the temperature range of 400° C. to 300° C. LT Greater than 4s, preferably greater than 8s, especially greater than 12s; 1) Optionally, the coated flat steel product is temper-rolled.
9. The method according to claim 8, characterized in that The ratio of the Al content to the sum of the Nb and V contents of the slab or thin slab, Al / (Nb+V), is: Al / (Nb+V)≤30.
0.
10. The method according to claim 8 or 9, characterized in that In the hot-dip coating operation, a melt bath is used which contains a corrosion protection agent which is applied in liquid form to the flat steel product and which consists of 0.1 to 15% by weight of Si, optionally 2 to 4% by weight of Fe, optionally up to 5% by weight of alkali metals or alkaline earth metals, optionally up to 10% by weight of Zn, optional further components whose contents are limited to a total of not more than 2.0% by weight, and the remainder of aluminum.
11. A metal formed sheet metal part formed from a flat steel product, the flat steel product comprising a steel substrate, the steel substrate consisting of steel, the steel consisting of iron and inevitable impurities, optionally one or more of the elements "Ce, La, Nb, Cr, Cu, Mo, Ni, Ca, W", and the following components in wt. %: C:0.06%-0.5%, Si: 0.05%-0.6%, Mn: 0.4%-3.0%, Al:0.06%-0.35%, B:0.0005%-0.01%, V:0.010%-0.50%, P:≤0.03%, S:≤0.02%, N:≤0.02%, Sn: ≤0.03%, As: ≤0.01%, The content of one or more of the optional elements "Ce, La, Nb, Cr, Cu, Mo, Ni, Ca, W" is: Ce+La: 0.01%-0.03%, Ti: 0.0005%-0.10%, Nb: 0.001%-0.2%, Cr:0.01%-1.0%, Cu: 0.01%-0.2%, Mo: 0.002%-0.3%, Ni: 0.01%-0.5%, Ca: 0.0005%-0.005%, W:0.001%-1.00%, Alternatively, the steel is composed of iron and inevitable impurities, optionally one or more of the elements "Al, Nb, Cr, Cu, Mo, Ni, Ca, W", and the following components in weight %: C:0.06%-0.5%, Si: 0.05%-0.6%, Mn: 0.4%-3.0%, B:0.0005%-0.01%, V:0.010%-0.50%, P:≤0.03%, S:≤0.02%, N:≤0.02%, Sn: ≤0.03%, As: ≤0.01%, Ce+La: 0.01%-0.03%, The content of one or more of the optional elements "Al, Nb, Cr, Cu, Mo, Ni, Ca, W" is: Al:≤1.0%, Ti: 0.0005%-0.10%, Nb: 0.001%-0.2%, Cr:0.01%-1.0%, Cu: 0.01%-0.2%, Mo: 0.002%-0.20%, Ni: 0.01%-0.5%, Ca: 0.0005%-0.005%, W:0.001%-1.00%。 12. The metal formed sheet component of claim 11 comprising a corrosion resistant coating.
13. The metal formed sheet component according to claim 11 or 12, wherein: The ratio of Al content to the sum of Nb and V content, Al / (Nb+V), is: Al / (Nb+V)≤30.
0.
14. The metal formed sheet metal component according to any one of claims 11 to 13, characterized in that The steel substrate of the metal profiled sheet metal component has a structure which at least partially comprises more than 90% martensite and / or lower bainite, preferably more than 95% martensite and / or lower bainite.
15. The metal formed sheet metal component according to any one of claims 11 to 14, characterized in that The metal profiled sheet metal part at least partially has a yield point of at least 950 MPa, in particular at least 1100 MPa, preferably at least 1200 MPa, in particular at least 1400 MPa, and / or The metal profiled sheet metal part at least partially has a tensile strength of at least 1000 MPa, in particular at least 1100 MPa, preferably at least 1300 MPa, preferably at least 1600 MPa, in particular at least 1800 MPa, and / or The metal profiled sheet metal part at least partially has an elongation at break A50 of at least 4%, preferably at least 5%, more preferably at least 6%, and / or The profiled metal sheet part at least partially has a bending angle of at least 30°, in particular at least 40°, preferably at least 45°, in particular at least 48°.
16. The metal profiled sheet metal component according to any one of claims 11 to 15, characterized in that The metal profiled sheet metal component has fine precipitates in its structure, in particular in the form of vanadium carbonitrides, niobium carbonitrides and / or titanium carbonitrides.
17. The metal formed sheet metal component according to any one of claims 11 to 16, characterized in that The fracture stress in the modified slow strain rate test is greater than 610 MPa, in particular greater than 625 MPa.
18. A method for producing a metal formed sheet metal component comprising the steps of: m) providing a sheet metal blank consisting of a flat steel product according to any one of claims 1 to 7; n) heating the sheet metal blank so that the AC3 temperature of the blank is exceeded at least to a certain extent and the temperature T of the blank when inserted into a forming tool provided for a hot press forming operation (step c)) is ins at least partially at a temperature above Ms+100° C., wherein Ms represents the martensite start temperature; o) Inserting the heated sheet metal blank into the forming tool, wherein the transfer time t required for removing the blank from the heating device and inserting the blank is trans No more than 20s, preferably no more than 15s; p) hot press forming a sheet metal blank to obtain a sheet metal formed part, wherein the blank is cooled during the hot press forming process at a cooling rate r at least partially greater than 30 K / s. tool The period t lasting more than 1s tool Cool to target temperature T target , and optionally maintained at that temperature; q) Remove from the tool and cool to the target temperature T target Metal formed sheet metal parts.
19. The method of claim 18, wherein: The temperature reached at least to a certain extent in the sheet metal blank in step b) is from Ac3 to 1000° C., preferably from 850° C. to 950° C.
20. The method of claim 18 or 19, wherein: The target temperature T of the metal forming sheet part target At least to some extent, it is lower than 400°C, preferably lower than 300°C.
Citation Information
Patent Citations
Shaped sheet-metal part with a high tensile strength formed from a steel and method for the production thereof
WO2019223854A1
Component produced by forming a sheet steel blank, and method for the production of said component
WO2020239905A1